Position specific physical demands in different phases of competitive matches in national level women's football - Juho K. Mäkiniemi; Eero H. J. Savolainen; Taija Finni; Johanna Ihalainen (Termedia Publishing House, 2022)
The purpose of the present study was twofold: to investigate position-specific physical match demands of national level women's football; and to examine if demands change during a match (comparison between first and second half and in 15-minute intervals). Seven teams from the Finnish National League participated in the study. Eighty-five players met the inclusion criteria, and a total of 340 individual match observations from 68 individual matches were included for analysis. The Polar Team Pro -player tracking system (with 10 Hz GPS units, including 200 Hz tri-axial accelerometer, gyroscope, magnetometer and HR monitor) was used to assess positional data and HR response of the players. This study demonstrated that women's national level football matches place a range of physical demands on players, which in general were highest for wide midfielders, and lowest for central defenders. Wide midfielders and forwards performed significantly more 'very high-speed' running, sprinting, accelerations, and decelerations than other outfield positions (p < 0.05). HRmean varied from 84-87% of HRmax and was significantly lower for central defenders than central midfielders (p < 0.001). External load variables varied during a match and generally decreased especially after 60 minutes of play compared to first 15-min period of the match. Present study showed that national level women football players' positional differences in match demands are similar to those reported with elite players in previous studies. On national level, players' physical performance tended to decrease towards the end of the match, especially in terms of total distance (~10%), high-speed running (~20%), and decelerations (~20%).